대답:
# (x-3) / (x + 3) #
설명:
먼저 모든 다항식을 인수로 얻습니다.
# 4x ^ 2-1 = (2x-1) (2x + 1) #
# x ^ 2-6x + 9 = (x-3) ^ 2 #
의 0을 찾아 봅시다.
1) # 2x ^ 2-5x-3 # 과 2) # 2x ^ 2 + 5x-3 # 2 차 방정식:
# x = (5 + -sqrt (25 + 24)) / 4 = (5 + -7) / 4 #
# x_1 = -1 / 2; x_2 = 3 #
그때
1) (x + 1 / 2) (x-3) = (2x + 1) (x-3) # 2x-2x-
#x = (- 5 + -sqrt (25 + 24)) / 4 = (- 5 + -7) / 4 #
# x_1 = -3; x_2 = 1 / 2 #
그때
2) # 2x ^ 2 + 5x-3 = 2 (x + 3) (x-1 / 2) = (x + 3) (2x-1) #
그러면 주어진 표현식은 다음과 같습니다.
# (취소 ((2x + 1))) / 취소 ((2x + 1)) 취소 ((x-3))) * ((x-3) ^ 취소 2) / (x + 3) cancel ((2x-1))) #
# = (x-3) / (x + 3) #